An improved collaborative movie recommendation system using computational intelligence - Wang, Zan; Yu, Xue; Feng, Nan; Wang, Zhenhua (Journal of visual languages and computing, 2014)
Recommendation systems have become prevalent in recent years as they dealing with the information overload problem by suggesting users the most relevant products from a massive amount of data. For media product, online collaborative movie recommendations make attempts to assist users to access their preferred movies by capturing precisely similar neighbors among users or movies from their historical common ratings. However, due to the data sparsely, neighbor selecting is getting more difficult with the fast increasing of movies and users. In this paper, a hybrid model-based movie recommendation system which utilizes the improved K-means clustering coupled with genetic algorithms (GAs) to partition transformed user space is proposed. It employs principal component analysis (PCA) data reduction technique to dense the movie population space which could reduce the computation complexity in intelligent movie recom-mendation as well. The experiment results on Movielens dataset indicate that the proposed approach can provide high performance in terms of accuracy, and generate more reliable and personalized movie recommendations when compared with the existing methods. •Proposed an optimized clustering algorithm to partition user profiles.•To represent denser profile vectors by principal component analysis transforming.•Be examined to provide high prediction accuracy and more reliable recommendations.